2010
DOI: 10.1136/emj.2009.081497
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Manchester Triage in acute myocardial infarction: impact on prognosis

Abstract: MT proved to be an effective system. Patients with typical AMI presentation, ST elevation myocardial infarction and less than 70 years old are protected by MT, with lower ITTFO and better short-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
25

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 11 publications
2
26
2
25
Order By: Relevance
“…Similarly, other studies (3,(11)(12)14,18,20) have already shown an association between priority attributed by the MTS and severity levels (18,20) , risk of remaining hospitalized (11)(12)18,20) , length of hospital stay (18) , and risk of death (11)(12)18,20) . One of these studies (18) proved that the mean of number of days of hospital stay decreased in the same order of complexity of patient status ( red, orange, yellow, and green).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, other studies (3,(11)(12)14,18,20) have already shown an association between priority attributed by the MTS and severity levels (18,20) , risk of remaining hospitalized (11)(12)18,20) , length of hospital stay (18) , and risk of death (11)(12)18,20) . One of these studies (18) proved that the mean of number of days of hospital stay decreased in the same order of complexity of patient status ( red, orange, yellow, and green).…”
Section: Discussionmentioning
confidence: 54%
“…The time for nurses to undertake RC is also recommended, and should not exceed three minutes (1)(2) . Some studies (3)(4)(5) have already assessed the time between risk classification and first medical care in specific situations such as myocardial infarction, as well as outcomes of patients studied. However, studies with a focus on the assessment of time between the arrival of patients at emergency medical services and their classification, as well as the time spent on RC, which is a stage undertaken by nurses, cannot be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Four (80%) studies were conducted with adults (12,(14)(15)(16) and one (20%) with a pediatric population (13) . Of the nine articles on validity of MTS, five (55.5%) were performed in the Netherlands (18)(19)22,(24)(25) , three (33.3%) in Portugal (20)(21)23) and one (11.2%) in Brazil (17) . Four (44.5%) studies were conducted with adult populations (17,(20)(21)23) , three (33.3%) in the pediatric population (19,(24)(25) and two (22.2%) with adult and pediatric populations (18,22) .…”
Section: Resultsmentioning
confidence: 99%
“…This was measured by reference to the following outcomes: evolution of condition/illness severity (17) ; sensitivity and specificity (18,21) ; percentage of overtriage and undertriage (15,18,(24)(25) ; necessity of hospitalization (19,(22)(23) and mortality rate (20,23) . A study (17) that correlated the classification of the patient obtained using the MTS with the same level of severity measured by the Therapeutic Intervention Scoring System (TISS -28) instrument.…”
Section: VImentioning
confidence: 99%
See 1 more Smart Citation